2019
DOI: 10.31236/osf.io/daq6n
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The effects of cluster-set and traditional-set post activation potentiation protocols on vertical jump performance

Abstract: Purpose. To compare the acute effects of two post activation potentiation (PAP) protocols using traditional or cluster-set configurations on countermovement jump (CMJ) performance. Methods. Twenty-six male basketball players were evaluated on three occasions separated by 72 hours. On the first session, athletes performed barbell squat jumps with progressively heavier loads to determine their individual optimum power loads. On the second and third sessions, athletes completed two PAP protocols in a randomized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Parallel to this study findings, McCann and Flanagan (20) found that 4-minute recovery duration was significantly better than 5-minute recovery duration in terms of baseline vertical jump height. Iacano et al (15), who compared the acute effects of 2 PAP protocols using traditional or cluster-set configurations on CMJ performance, also found vertical jump heights showed significant increases, (by between 3.7 and 4.2%) after 4 minutes of recovery compared with baseline vertical jump heights. This study findings thus support previous research which has suggested that a 4minute recovery is advised between the high-intensity resistance exercise and subsequent explosive tasks such as jump and sprint performances to observe increased power output (28,31).…”
Section: Discussionmentioning
confidence: 95%
“…Parallel to this study findings, McCann and Flanagan (20) found that 4-minute recovery duration was significantly better than 5-minute recovery duration in terms of baseline vertical jump height. Iacano et al (15), who compared the acute effects of 2 PAP protocols using traditional or cluster-set configurations on CMJ performance, also found vertical jump heights showed significant increases, (by between 3.7 and 4.2%) after 4 minutes of recovery compared with baseline vertical jump heights. This study findings thus support previous research which has suggested that a 4minute recovery is advised between the high-intensity resistance exercise and subsequent explosive tasks such as jump and sprint performances to observe increased power output (28,31).…”
Section: Discussionmentioning
confidence: 95%
“…The main findings of this study showed that performing either traditional or cluster set configuration did not affect the main parameters of the countermovement jump. Many research studies been conducted the effect of cluster set during resistance training or plyometric training on athlete performance [14,20,24,25,26,27]. However, the literature on the effect of cluster set on the complex training is scant and does not provide clear conclusion in regards to the acute effect of cluster set on power performance [15,28].…”
Section: Discussionmentioning
confidence: 99%
“…A randomized cross-over design was used to compare the effects of three PAPE protocols implementing jump squats loaded with OPL as the conditioning activity but executed using different configurations: i) traditional, in which the sets and repetitions completed are aligned with the contemporary PAP literature, [3][4][5][6][8][9][10] ii) self-selected, in which subjects were allowed to choose the number of repetitions completed in each set, and iii) imposed, in which the number of repetitions completed matched those of the self-selected condition, but imposed on subjects prior to the beginning of the session, rather than self-selected during each set. The effects of the three protocols were compared on subsequent vertical jump performance asssessed by the squat jump test.…”
Section: Designmentioning
confidence: 99%
“…Then, jump squat warm up sets with progressively heavier loads were performed. The same instructions recently described by Dello Iacono et al, 10 were used for the jump squat execution. The OPL were assessed following the protocol described by Loturco et al, 20 on a Smith machine (Technogym Equipment, Italy).…”
Section: Optimum Power Load Assessmentmentioning
confidence: 99%
See 1 more Smart Citation